Spatial and non-spatial aspects of neglect - Carlo Umilta (Frontiers Research Topics, 2015)
Neglect is one of the most impressive neuropsychological disorder, for both its theoretical and clinical relevance. Besides being very common and disabling, it is highly informative for understanding normal cognitive functioning. The hallmark of neglect is the failure to attend to the contralesional hemispace. However, several studies have recently highlighted that additional deficits, not attributable to a spatial bias, are associated to the impaired contralesional hemispace processing. Moreover, manifestations of neglect tend to be particularly heterogeneous and often dissociate according to the spatial domain being investigated (e.g., body space, space within reaching, space beyond reaching, imaginal space). Heterogeneity in neglect patients also means that dissociations across different tasks in a single patient are more the rule than the exception. Evidence suggests that some of these dissociations can be readily explained by taking into account the amount of available attentional resources as a major determinant for the presence and the severity of neglect. There is no doubt that neglect patients provide a wealth of information about the functioning of systems subserving attentional orienting and spatial processing. Moreover, their performance also show that some non-spatial deficits are tightly coupled with more classic contralesional spatial deficits. It seems however still unclear to what extent these non-spatial deficits are an intrinsic characteristic of neglect or whether they are to be considered unspecific effects of the often massive brain lesions suffered by the patients. From the clinical point of view, neglect is a disorder that dramatically affects patients and their caregivers, because it severely limits the individuals' autonomy and motor recovery after brain damage. For these reasons neglect is a disorder that is worth rehabilitating. To be effective, neglect rehabilitation should be based on the knowledge of what cognitive aspects are impaired and it should be focused on improving daily-life performance. For these reasons, it is also important to detect and quantify subtle forms of neglect.